Potential Activity of 3-(2-Chlorophenyl)-1-phenyl-propenonein Accelerating Wound Healing in Rats. (22nd January 2014) - Dhiyaaldeen, Summaya M.; Alshawsh, Mohammed A.; Salama, Suzy M.; Alwajeeh, Nahla S. I.; Al Batran, Rami; Ismail, Salmah; Abdulla, Mahmood Ameen
Abstract : Wound healing involves inflammation followed by granular tissue development and scar formation. In this study, synthetic chalcone 3-(2-Chlorophenyl)-1-phenyl-propenone (CPPP) was investigated for a potential role in enhancing wound healing and closure. Twenty-four male rats were divided randomly into 4 groups: carboxymethyl cellulose (CMC) (0.2 mL), Intrasite gel, and CPPP (25 or 50 mg/mL). Gross morphology, wounds treatment with the CPPP, and Intrasite gel accelerate the rate of wound healing compared to CMC group. Ten days after surgery, the animals were sacrificed. Histological assessment revealed that the wounds treated with CPPP showed that wound closure site contained little amount of scar and the granulation tissue contained more collagen and less inflammatory cells than wound treated with CMC. This finding was confirmed with Masson's trichrome staining. The antioxidant defence enzymes catalase (CAT) and superoxide dismutase (SOD) were significantly increased in the wound homogenates treated with CPPP (P < 0.05 ) compared to CMC treated group. However, in the CPPP treatment group, lipid peroxidation (MDA) was significantly decreased (P < 0.05 ), suggesting that the CPPP also has an important role in protection against lipid peroxidation-induced skin injury after ten days of treatment with CPPP, which is similar to the values of cytokines TGF- β and TNF- α in tissue homogenate. Finally the administration of CPPP at a dosage of 25 and 50 mg/kg was suitable for the stimulation of wound healing.